Dual MGMT inactivation by promoter hypermethylation and loss of the long arm of chromosome 10 in glioblastoma. (14th July 2020) - Richard, Sophie; Tachon, Gaëlle; Milin, Serge; Wager, Michel; Karayan‐Tapon, Lucie
Abstract: Background: Epigenetic inactivation of O6‐methylguanine‐methyltransferase ( MGMT ) gene by methylation of its promoter is predictive of Temozolomid (TMZ) response in glioblastoma (GBM). MGMT is located on chromosome 10q26 and the loss of chromosome 10q is observed in 70% of GBMs. In this study, we assessed the hypothesis that the dual inactivation of MGMT, by hypermethylation of MGMT promoter and by loss the long arm of chromosome 10 (10q), may confer greater sensitivity to TMZ. Methods: A total of 149 tumor samples from patients diagnosed with GBM based on the WHO 2016 classification were included in this retrospective study between November 2016 and December 2018. Methylation status of MGMT promoter was evaluated by pyrosequencing and status of chromosome 10q was assessed by array comparative genomic hybridization. Results: Glioblastoma patients with chromosome 10q loss associated with hypermethylation of MGMT promoter had significantly longer overall survival (OS) ( P = .0024) and progression‐free survival (PFS) ( P = .031). Indeed, median OS of patients with dual inactivation of MGMT was 21.5 months compared to 12 months and 8.1 months for groups with single MGMT inactivation by hypermethylation and by 10q loss, respectively. The group with no MGMT inactivation had 9.5 months OS. Moreover, all long‐term survivors with persistent response to TMZ treatment (OS ≥ 30 months) displayed dual inactivation of MGMT . Conclusions: Our data suggest that the molecular subgroup characterized by the dual inactivation of MGMT receives greater benefit from TMZ treatment. The results of our study may be of immediate clinical interest since chromosome 10q status and methylation of MGMT promoter are commonly determined in routine practice. Abstract : MGMT can be inactivated by two mechanisms: methylation of promoter and chr10q loss. Dual inactivation of MGMT selected a population with greater benefit from TMZ. Patients with long‐term OS (>30months) presented dual inactivation of MGMT. Chr10q status and methylation of MGMT are commonly determined in routine practice.